Brexit, Science and Higher Education: Legal Problems and Regulatory Dilemmas of Disintegration - Mark L. Entin; Dmitry V. Galushko (Современная Европа)
The purpose of the study is a dialectical consideration of the sphere of science and higher education as a factor influencing the development of integration interaction between integration entities and member states and preventing disintegration. The authors substantiate that over the years of EU membership, the United Kingdom has become a highly integrated state that has received numerous benefits in the field of science and higher education, for which Brexit can be considered a step back. The concluded agreements between London and Brussels, as well as the adopted British legislation, on the one hand, contributed to a decrease in the flow of students and representatives of the academic community to the UK, and on the other, became an obstacle to the UK’s participation in projects for organizing mobility and developing the potential of universities within the framework of EU educational and research programs, previously making up a significant portion of UK university funding. As a result, the British government did not give up attempts to restore a high degree of interaction with the EU in this area. Following Windsor Framework Agreement, the two parties agreed on UK’s participation in European programs on an equal basis with colleagues from EU member states and access to appropriate funding, which, however, only partially compensates for the negative consequences of ending membership in EU. The authors emphasize that Brexit confirms that international interaction in science and higher education is an important factor in strengthening integration construction, which is fully relevant for the development and strengthening of integration of states within the Eurasian Economic Union.